Polyneuropathy in hypothyroidism. Issue 694 (August 1983) - Dick, D. J.; Lane, R. J.; Nogues, M. A.; Fawcett, P. R.
Abstract : A patient who developed symptoms and signs of a polyneuropathy was found to have hypothyroidism, though this diagnosis was not clinically suspected. Treatment with thyroxine resulted in resolution of his symptoms and restored his nerve conduction studies to normal.